KADAR GLUKOSA, UREUM DAN LIPIDA DARAH SAPI BALI YANG DIBERI RANSUM DIFERMENTASI DENGAN INOKULAN BAKTERI LIGNOSELULOLITIK RUMEN DAN RAYAP - I K. G., Suyasa; Mudita, I M.; Siti, N. W.; Wirawan, I W. (Jurnal Peternakan Tropika; Vol 4 No 2 (2016), 2016)
The study aimed to determine the effect of ration fermented inoculant lignocellulolytic bacteria rumen and termites on levels of glucose, urea and blood lipids bali cattle have held in Station Research of Animal Husbandry Faculty, Udayana University, Bukit Jimbaran. The research used three elected superior inoculant (BR 23 T 14 , BR 24 T 13 , BR 34 T 12 ) result research by Mudita et al . (Unpublished). The experiment was conducted using a randomized block design (RBD) with three treatments and three groups as replication. The treatments were RF1 was ration fermented with superior inoculant 1 (BR 23 T 14 ), RF2 was ration fermented with superior inoculant 2 (BR 24 T 13 ) and RF3 was ration fermented with superior inoculant 3 (BR 34 T 12 ). The variables measured include concentration level of glucose, urea, cholesterol, triglycerides, HDL and LDL blood of Bali cattle. The results showed that the ration fermented by third superior inoculant (RF1, RF2 and RF3) capable of producing concentration of glucose, urea and blood lipids (cholesterol, triglycerides, HDL and LDL) were not significant different (P>0.05). Based on the results of this study concluded that given ration fermented by third inoculant of lignocelluloliytic bacteria rumen and termites does not lead to differences in the blood chemistry profile especially glucose, urea and blood lipids bali cattle.
Keywords: Lignocellulolityc Bacteria, Inoculant, Blood Chemistry Profile, Rumen, Termite.